The Role of The Madrasah Head In Improving Teachers' Work Ethic In Teaching at MTs Al-Washliyah Tandam Hilir, Hamparan Perak, Deli Serdang - Robin Sirait; Satriyadi Satriyadi; Indra Satia Pohan; San Putra (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims to describe the role of the madrasa head in improving the work ethic of teachers at MTs Al-Washliyah Tandam Hilir. The method used in this research is qualitative descriptive research. Data collection uses observation, interviews and documentation studies methods. The results of this research show that the role of the madrasa head in improving the work ethic of teachers in teaching at MTs Al-Washliyah is by meeting the teacher's financial needs, then the madrasa head also gives rewards to teachers who are considered the most active in terms of attendance and discipline in carrying out their duties. Another thing that is done is providing training in curriculum development for subjects according to the field of study, in order to improve the professional quality of teachers, so that teachers can improve their work ethic in teaching. The obstacle faced is that there are still teachers who often arrive late and lack discipline in teaching. Then there are still some teachers who are not academically aligned with the subjects they teach. The solution offered as an improvement effort in overcoming the obstacles that occur is that the head of the madrasah provides punishment or administrative sanctions for teachers who are undisciplined and often come to school late. Discuss with the madrasa supervisors regarding policies for teachers who are not yet aligned with their academic fields.